Development of plant-based cookies free of allergenic ingredients with rice flour and beetroot (Research, Society and Development, 2025)
The objective was to evaluate the effect of partially replacing rice flour (RF) with beet flour (BF) on the technological characteristics of gluten-, milk-, and egg-free cookies. Five formulations with different proportions of RF and BF were developed: F1 (100:0), F2 (98.5:1.5), F3 (97:3.0), F4 (95.5:4.5), and F5 (94:6.0). Moisture, water activity (WA), and color of the flours and corn starch (CS) were evaluated, as well as moisture, WA, specific volume (SV), texture, and color of the cookies. The flours and CS had moisture content between 6.13% and 12.90%, within standards, and WA below 0.63, which prevents microbial growth. BF had a dark red hue, while RF and CS tended to be white. The increasing addition of BF did not show linear behavior in relation to moisture values (12.68–17.24%) and WA values (0.72–0.84). However, it increased SV (from 1.32 to 1.57 cm³·g⁻¹), reduced the expansion factor (from 2.83 to 2.17) and hardness (from 12.55 N to 7.59 N), making the cookies less crunchy. The incorporation of BF intensified the red color of the cookies, proportional to the level of substitution. The formulation with 3% BF (F3) presented acceptable technological characteristics, not influencing SV, and hardness, in addition to giving an attractive color due to betalains, natural pigments present in beetroot. Thus, the partial replacement of RF with BF proves to be a viable alternative to produce gluten-, milk-, and egg-free cookies with potentially better nutritional value.